Extraction of Natural Dyes for the Application in Dye Sensitized Solar Cells (DSSCs) - Jaya Krishna, Thasarathan (Universiti Teknologi PETRONAS, 2016)
In this report, the turmeric and Areca Catechu, commonly known as kunyit and biji pokok pinang were chosen for extraction of natural dyes, as the dyes extracted from these plant sources can be used to study their efficiency in capturing solar energy for the application in dye sensitized solar cells (DSSC). The research revolves around finding the appropriate solvent in which both natural dyes can be extracted at greater yield, conducting UV-VIS analysis to study on absorption spectra of both dyes, to distinguish the influence of pH and temperature on extraction of natural dyes as well as highlighting the energy conversion of both dyes in a DSSC. As such, the extraction of both natural dyes are performed via solvent extraction method where different types of solvents were used in order to study their extraction efficiency namely Methanol, Ethanol, Acetone and water. For pH study, the dyes are treated with hydrochloric acid in order to determine an optimum pH at where both dyes function best.